Inhibiting Factors of the Implementation of 14 T in Pregnant Women at Puskesmas Padongko, District Barru - Alya Risma (Manunggal Halim Jaya, 2021)
This study aims to determine the effect of inhibiting factors on the implementation of 14 T in pregnant women at Padongko Health Center in Barru District. This research is quantitative research through a descriptive-analytic approach with the research method of